2019
DOI: 10.1039/c9cc07829k
|View full text |Cite
|
Sign up to set email alerts
|

A palladium–carbon-connected organometallic framework and its catalytic application

Abstract: A Pd–C-bond-connected organometallic framework and its catalytic activity for the Suzuki–Miyaura cross-coupling reaction were reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…The CNDipp CC Ar and CN-1-(2- i Pr)-Naph arylisocyanide ligands of interest in this work are depicted in Figure . The former were prepared according to modified literature procedures. ,, Like their CNDippAr counterparts, all CNDipp CC Ar ligands can be prepared from the same readily accessible synthetic intermediate, N -formyl-4-iodo-2,6-diisopropylaniline. Sonogashira coupling of this reagent with phenylacetylene, 1-naphthylacetylene, 9-phenanthrenylacetylene, 4-methoxyphenylacetylene, or 4-cyanophenylacetylene, followed by dehydration of the resulting formamide with OPCl 3 , yields the isocyanide ligands CNDipp CC Ph, CNDipp CC -1-Naph, CNDipp CC -9-Phen, CNDipp CC Ph OMe , and CNDipp CC Ph CN , respectively, in moderate yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…The CNDipp CC Ar and CN-1-(2- i Pr)-Naph arylisocyanide ligands of interest in this work are depicted in Figure . The former were prepared according to modified literature procedures. ,, Like their CNDippAr counterparts, all CNDipp CC Ar ligands can be prepared from the same readily accessible synthetic intermediate, N -formyl-4-iodo-2,6-diisopropylaniline. Sonogashira coupling of this reagent with phenylacetylene, 1-naphthylacetylene, 9-phenanthrenylacetylene, 4-methoxyphenylacetylene, or 4-cyanophenylacetylene, followed by dehydration of the resulting formamide with OPCl 3 , yields the isocyanide ligands CNDipp CC Ph, CNDipp CC -1-Naph, CNDipp CC -9-Phen, CNDipp CC Ph OMe , and CNDipp CC Ph CN , respectively, in moderate yield (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…34−44 Accordingly, despite their charge neutrality, the dual bonding interactions provided by isocyanides lead to strong metal−ligand linkages that can be harnessed for reticular network formation. 24,25,45 It was shown that [CNAr Mes2 ] 2 could provide a series of robust, singlecrystalline frameworks featuring Cu(I)-based single-metal structural nodes (i.e., Cu-ISO CNs 1−3; ISO CN = isocyanide coordination network; Scheme 1). 24 In certain cases, these frameworks retain their thermal integrity up to ca.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, we reported an approach to overcoming this challenge by using the rigid and linear ditopic m -terphenyl diisocyanide, [CNAr Mes2 ] 2 , as a linker group (Ar Mes2 = 2,6-(2,4,6-Me 3 C 6 H 2 ) 2 C 6 H 3 ; Scheme ). , Isocyanide ligands have long been recognized for their ability to function as both good σ-donors and strong π-acids, which are properties that are particularly advantageous for the stabilization of electron-rich metal centers. Accordingly, despite their charge neutrality, the dual bonding interactions provided by isocyanides lead to strong metal–ligand linkages that can be harnessed for reticular network formation. ,, It was shown that [CNAr Mes2 ] 2 could provide a series of robust, single-crystalline frameworks featuring Cu­(I)-based single-metal structural nodes (i.e., Cu- ISO CNs 1–3; ISO CN = isocyanide coordination network; Scheme ). In certain cases, these frameworks retain their thermal integrity up to ca.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Dong and co-workers reported a 2D Pd II LVMOF formed by the solvothermal reaction between a tritopic isocyanide linker and PdI 2 . [58] This LVMOF was applied as a heterogeneous catalyst for Suzuki-Miyaura coupling to produce substituted biphenyls. Significantly, in comparison to molecular Pd-isocyanide catalysts, the LVMOF required lower reaction temperatures, shorter [51] B) synthesis and crystal structure of Cu-ISO CN-4 highlighting 3-connected Cu I node and extended structure of a single 2D sheet; [52] C) synthesis and crystal structure of Ni-ISO CN-2 with view of extended structure and tetrahedral Ni 0 nodes.…”
Section: Methodsmentioning
confidence: 99%